Analysis of Antibacterial Test and Brine Shrimp Lethality Test from Extract Sponge Derived Fungi - Oktora Susanti; Nisa Karima; Ervina Damayanti (Jurnal Biologi Tropis, 2026)
Bacterial resistance to antibiotics has increased the demand for new antibacterial agents from natural sources, including marine organisms. This study evaluated the antibacterial activity and toxicity of sponge-associated fungal extracts. Antibacterial activity against Escherichia coli was tested using the disc diffusion method, while toxicity was assessed using the Brine Shrimp Lethality Test (BSLT). The extract was obtained by maceration with 95% methanol and tested at various concentrations. The extract showed antibacterial activity, with the largest inhibition zones at 100 and 1,000 ppm after 24 hours, which decreased after 48 hours. BSLT results showed 100% mortality of Artemia salina larvae at concentrations ≥100 ppm. The main BSLT test revealed a dose–response relationship, with higher doses and longer exposure reducing larval survival. These results indicate that sponge- associated fungal extracts are promising antibacterial agents, although their toxicity requires further evaluation.